Crop productivity as affected by fertilizer management options in Boro -T.aman cropping pattern at farmers' fields (Bangladesh Journal of Agricultural Research, 2010)
The experiment was conducted at multilocation testing (MLT) site, Sujanagar, Pabna during the year of 2003-2004 to find out a soil test based economically viable fertilizer recommendation for the cropping pattern Boro-T. aman. Six treatments viz., moderate yield goal (MYG), high yield goal (HYG), integrated plant nutrient system (IPNS), recommended fertilizer of FRG' 97 (BARC) guide (RF), farmers' practice (FP), and absolute control were employed for the study. The grain yield of Boro and T. aman rice increased 18 and 14%, respectively, by IPNS compared to farmers' practice. Total grain yield of rice was increased by about 16% in the IPNS fertilizer package compared to farmers' practice. Fertilizer nutrients supplied both from organic and inorganic sources in adequate amount have a positive effect on productivity of soil. On an average it was found that highest grain yields of Boro rice (5.37 t/ha) and T. aman (4.49 t/ha) were obtained from integrated plant nutrient system (IPNS) where farmers’ practice gave yield of 4.55 and 3.94 t/ha. The highest average gross margin (70385 Tk./ha) and marginal benefit cost ratio (3.78) was also obtained from IPNS plots. Keywords: Crop productivity; fertilizer management; cropping pattern. DOI: 10.3329/bjar.v35i2.5892Bangladesh J. Agril. Res. 35(2) : 287-296, June 2010